Pengaruh Input-Input Variabel terhadap Hasil Produksi Maksimum dengan Pendekatan Jangka Panjang dalam Perspektif Islam (Studi Kasus Pada Usaha Home Industri Tenun Di Kecamatan Tanasitolo Kabupaten Wajo) - Kartini Kartini (Jurnal Ilmiah Al-Tsarwah : ilmu ekonomi dan keuangan (konvensional dan syariah), 2018)
This study aims to determine the effect of variable inputs on maximum production results with a long-term approach in the Islamic perspective (Case Study in Weaving Home Industry Enterprises in Tanasitolo District, Wajo Regency). The subject matter of study is the influence of variable inputs on production output. Based on the objectives of the research above, the type of research used is field research using a quantitative approach supported by observation methods, and questionnaires in collecting the required data. The collected data is then processed using statistical analysis and then interpreting the data using the SPSS version 21 program for Windows. The analytical method used in this study is simple linear regression in knowing the magnitude of the change in a variable against other variables with the help of SPSS version 21 for Windows. Calculations carried out to measure the proportion or percentage of the total variation of the dependent variable that can be explained by the regression model. The results of the study show that, partially, the variable inputs have a significant effect on the production of the Weaving Home Industry Kec. Tanasitolo District of Wajo because t table t count (0.294 1.508) this indicates H1 is accepted and H0 is rejected. Regression analysis shows that simultaneously, the variable inputs have a significant effect on the yield of the Kec. Weaving Home Industry. Tanasitolo District of Wajo where significance is significance level (0,000 0,1), this indicates that H1 is accepted and H0 is rejected.